Spatial Terms: The Acquisition of Multiple Referential and Syntactic Mappings - Shimpi, Priya; Waterfall, Heidi (Frontiers in Communication, 2019)
The current study used a naturalistic, longitudinal design to investigate how children and parents use a set of early-acquired spatial terms (up, down, in, out, on, off). Measures included the frequency, referential contexts, syntactic frames, and referent-syntax pairings of these words from 14 to 30 months. Results showed that children’s earliest use of these terms related to parents’ referential use, but not to parent frequency of use. During the multi-word period, parent frequency of spatial term use was reflected in children’s frequency of use. Further, children’s most frequent referent-syntax pairings were predicted by these pairings in parents’ speech. The current results indicate that children may initially use referential cues in the acquisition of these terms, and later become sensitive to the relative frequencies of referent-syntax pairings for individual lexical items. This study demonstrates how children use regularities across multiple sources of information in the input during acquisition.